An Iraqi by Birth, an Israeli in Body, a Soul without Borders. Sason Shaik in His Own Words. Issue 9 (31st May 2022) - Seeman, Jeffrey I.
Abstract: This paper consists of a compilation of several interview with the eminent theoretical chemist Sason Shaik of The Hebrew University of Jerusalem. Shaik has published many original research articles, reviews, book chapters, and books that extensively discuss his science. To broaden the knowledge and understanding of Sason Shaik, these interviews and this paper focus almost entirely on him as a human being. Abstract :